Management of the Energy Business in the Countries with Developing Economies in the Conditions of the Integration Processes - Shulus, Aleksei A.; Doguchaeva, Svetlana M.; Gukasyan, Gurgen L.; Bobkov, Aleksandr V.; Prasolov, Valeriy I. (International Journal of Energy Economics and Policy, 2019)
The present article describes the problems, which are connected with consequences of the ever-increasing influence of the world integration processes upon the national economies in the sphere of energy business. At the global level, this influence is evident as the dependency of governmental budgets of the oil and gas sector from commercial interests of the international corporations, which are owners of the production enterprises in the countries with developing economies. Moreover, it creates new vectors and trends of development both for entire industry and for power markets particularly. Goal of this article is to test this hypothesis on the basis of the corporate structured approach with the help of statistical and financial methods and instruments. Another goal of this article is to determine degree of influence of corporations upon national economies of developing countries in the power-generating sector. As the result, we have succeeded in improvement of the LRD (Limited Risk Distributor), which is the model of the corporate business management. This model is topical one and it is applicable for any energy companies within corporate entities (holdings and groups of companies) in the countries with developing economies. Keywords: energy business; emerging markets; corporations; LRD management business model. JEL Classifications: F23; F36; G34; O13 DOI: https://doi.org/10.32479/ijeep.7789